Understanding Broad Consent - Maloy, John W.; Bass, Pat F. (The Ochsner journal, 2020)
The 2018 revisions to the Common Rule that were effective in January 2019 introduced a new category of informed consent: broad consent. Investigators and institutional review board (IRB) members need to understand (1) what broad consent is, (2) the role of broad consent under the revised Common Rule, (3) how and when broad consent can be used, (4) exempt research categories that relate to broad consent, and (5) the scope of limited IRB review as it relates to broad consent. Under the prior regulations, researchers had two consent options: obtain study-specific informed consent or request the IRB to waive the requirement to obtain informed consent. The revision to the Common Rule introduced the third option of broad consent, but its applicability is limited. Broad consent can only be used to obtain an individual's consent for the storage, maintenance, and secondary research use of identifiable private information or identifiable biospecimens. The regulatory authority for broad consent is at 45 CFR §46.116(d). None of the required elements of broad consent can be omitted or altered because each element is considered essential. Broad consent shares many of the requirements for study-specific informed consent, but several elements are unique: a description of the types of secondary research that may be conducted; statements describing the private information or biospecimens that might be used in research, whether sharing of the information or biospecimens might occur, and the types of institutions or researchers that might conduct research with the information or biospecimens; information on how long the information or biospecimens may be stored, maintained, and used; a statement that subjects will or will not be informed of the details of any subsequent research; a statement that research results will or will not be disclosed to subjects; and contact information for obtaining answers to questions about the subjects' rights regarding storage and use of information or biospecimens and whom to contact regarding research-related harm. Broad consent provides flexibility that did not exist prior to the revision, giving researchers the option to obtain broad consent for the storage, maintenance, and secondary research use of identifiable private information or identifiable biospecimens. With an understanding of the regulations, an investigator can plan how best to organize his or her research plan and decide whether to obtain study-specific informed consent, to apply for a waiver of consent, or to obtain broad consent.